Konsep Evaluasi Pendidikan dalam Perspektif Islam Berdasarkan Al-Qur'an dan Hadits - Yuniartin, Titin; Astuti, Erma Hari Tri; Alfinnas, Haflah (INCARE, International Journal of Educational Resources, 2024)
Islamic education evaluation is a crucial component in shaping the holistic character of students based on the values of the Qur'an and Hadith. This study aims to analyze the principles of Islamic education evaluation from this perspective, emphasizing justice, continuity, and the integration of worldly and spiritual values. The research employs a qualitative descriptive method with a library research approach, utilizing primary sources such as the Qur'an and Hadith alongside secondary references from relevant literature. The findings reveal that evaluation rooted in Qur'anic values not only measures intellectual achievements but also fosters integrity and spiritual piety. Justice serves as the core principle of evaluation, while a continuous approach enables students to reflect and develop comprehensively. These findings highlight the need for developing holistic evaluation instruments that align with modern educational demands while remaining consistent with Islamic values.